ANALYSIS OF TOURISTS' WILLING TO PAY IJEN CRATER NATURAL TOURISM PARK - Cardias, Esa Riandy; Sanjaya, Aditya Wiralatief; Ermawati, Eka Afrida; Yustita, Aprilia Divi (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Ijen Crater Natural Tourism Park/TWAKI (92 ha) is part of the Ijen Crater Nature Reserve area (2,468 ha) with various kinds of protected biota. In 2016 UNESCO designated Ijen Crater as one of the Biosphere Reserves of 120 countries in the world. All the uniqueness that TWAKI has means that tourist visits to this destination tend to increase significantly, and in the end the carrying capacity of the environment has been exceeded in the last four years. TWAKI is only able to accommodate 165,600 tourists per year based on its area. Therefore, proper management of the TWAKI is needed, to accommodate tourism functions and maintain main function as a nature conservation area, but a lot of funds are needed. Willingness to pay (WTP) tourists are expected as another source of funding outside the government. This study aims to analyze the level of WTP tourists. This research was designed using the Contingent Valuation Method (CVM), which is a survey method to ask tourists about the value or price they give to commodities that have no market value such as environmental goods. The results showed that the average WTP value for foreign tourists was US 28 and IDR 25.000 for domestic tourists, so that the economic value of ecotourism and estimated income from ticket sales based on the WTP value were US 864.528 or around 12 billion and IDR 3.776.800.000. Both values show values greater than the basic WTP value, which is calculated based on data on the number of tourists. This total value is also greater than the total budget required by TWAKI for maintenance, management and conservation costs.